Phenotypic and genotypic characterization of stereptococcus pneumoniae isolates among healthy children in Kuala Lumpur and Selangor, Malaysia - Mohd Yatim, Masura (2013)
There is scarce information about pneumococcal carriage among healthy children in Malaysia. The nasopharynx of human is well known as ecological reservoir of Streptococcus pneumoniae which is a precondition for developing pneumococcal diseases. Because the pneumococcal disease is common in children, this study was conducted to provide data on the prevalence rate, serotype distribution and antimicrobial susceptibility pattern of S. pneumoniae in the nasal carriage of healthy children. Further investigation such as pneumococcal surface protein A (PspA) family prevalence, clade distribution and its relatedness with pulsed-field gel electrophoresis (PFGE) patterns were also investigated. Nasal swabs were collected from 195 healthy children age 5 years old or younger from June to December 2010 in three day care centers in Kuala Lumpur and Selangor. All S. pneumoniae isolates were successfully identified by both phenotypic and genotypic methods. The serotyping was performed using Pneumotest kit (Statens Serum Institut, Copenhagen, Denmark) and the antimicrobial susceptibility pattern was determined by using the E-test method (AB Biodisk, Solna, Sweden). PspA family typing was done using polymerase chain reaction (PCR) and epidemiological study was investigated by PFGE.S. pneumoniae was found in the nasal carriage of 35.4% (69/195) of children and this revealed an increasing trend of carriage prevalence among healthy children in Malaysia. Among the 69 isolates, penicillin resistant S. pneumoniae (PRSP) and multidrug resistant (more than two classes of antibiotic) S. pneumoniae (MDRSP) was 23.2% and 20.3% respectively. All 16 PRSP isolates were resistant to erythromycin and 14 PRSPs (87.5%) were resistant to cotrimoxazole. The six most common serotypes were 6A, 23F, 19A, 6B, 19F and 15C which were found in 87% of all isolates. The high rate of PRSP and MDRSP supports the need for continuing surveillance of pneumococcal carriage. In fact, data on surveillance of antimicrobial susceptibility pattern as well as serotype distribution also changed from time to time, emphasizing the need for continuing a surveillance study to keep in track the current situation. Of the 69 isolates, 24.6% belonged to PspA Family 1, 71.0% were found to PspA Family 2 and 4.3% to PspA Family 3. With regard to vaccine serotypes coverage, 40.6% of the isolates belonged to serotypes included in the PCV7 and PCV10 and 81.1% included in the PCV13. Even though conjugate vaccines from up to 13 serotypes have been developed, they only represent a limited number of serotypes, whereas over 90 serotypes exist. Due to the high cost and limited coverage, more effort is being focused to search for future vaccine candidates such as protein based vaccines which could cover the whole population regardless of age as well as serotypes. By studying and exploring the pattern of distribution based on PspA typing, it would provide useful information for the suitability of this protein antigen as a vaccine candidate against pneumococcal population. In this finding, the major family was 1 and 2 (95.7%), thus making them suitable for future vaccines. In general, PFGE patterns of the pneumococcal isolates were genetically diverse, which suggest that the relationship between susceptibility pattern, PspA family types, PspA clades and PFGE patterns was independent.